2001
DOI: 10.1038/sj.bmt.1702782
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the immunocytochemical detection of contaminating tumor cells (CTC) in apheresis products of patients with high-risk breast cancer treated with high-dose chemotherapy and stem cell transplantation

Abstract: Summary:The aim of this study was to determine whether the detection of CTC in the apheresis product contribute significantly to treatment failure of patients with highrisk breast carcinoma treated with high-dose chemotherapy (HDC) and stem cell transplantation (SCT). Patients were with stage II and III adenocarcinoma of the breast with у10 axillary lymph nodes affected after primary surgery (у10 N+) who had received HDC with SCT. We analyzed retrospectively the presence of CTC as assessed by immunocytochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The failure to identify circulating breast cancer cells in patients with early-stage disease can lead to an improper therapy strategy, which can cause the recurrence of breast cancer [7, 8]. It can also cause the reinfusion of tumor cells, since peripheral blood stem cells for hematopoietic reconstitution are necessary in some breast cancer patients [7, 8]. Nevertheless, the quantification of these cells is extremely difficult because of the low frequency of these cells in blood [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The failure to identify circulating breast cancer cells in patients with early-stage disease can lead to an improper therapy strategy, which can cause the recurrence of breast cancer [7, 8]. It can also cause the reinfusion of tumor cells, since peripheral blood stem cells for hematopoietic reconstitution are necessary in some breast cancer patients [7, 8]. Nevertheless, the quantification of these cells is extremely difficult because of the low frequency of these cells in blood [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The patients in our series were mobilized during the recovery from induction cycles, when active metastatic disease was still present and the risk of contamination would theoretically be higher. Although the actual prognostic significance of contaminating tumor cells remains controversial, [24][25][26][27] we considered it appropriate to infuse an unselected cellular product immediately after the next one or two courses following collection, but not at a later time, when the tumor burden could have been markedly reduced by the treatment. In most of our patients, enough progenitors to support the whole SICT program could have been collected with a short series of leukaphereses in a single mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Most of the experience in this area is based on the study of apheresis products collected when patients who have responded to previous induction chemotherapy are about to be intensified. The patients in our series were mobilized during the recovery from induction cycles, when active metastatic disease was still present and the risk of contamination would theoretically be higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of distant recurrence is increased in patients with DTCs or CTCs [5]. It has been demonstrated that treatment with conventional [6,7] or high dose chemotherapy [8] in patients with breast cancer may reduce the number of DTCs/ CTCs and that relapse free survival is longer in patients without CTCs [8][9][10] Although it has been shown that the contamination of tumor cells in autologous grafts are responsible in posttransplant relapses, [11,12] the clinical significance of this finding is not known. The other way of reducing CTCs in autologous grafts is CD34 1 cell selection [13,14].…”
Section: Introductionmentioning
confidence: 97%